Caracterización de alternativas ecoturísticas en el cantón Salcedo provincia de Cotopaxi. - Jesús Benites, Leandro Andrés (2021)
This research focused on characterizing ecotourism alternatives at Salcedo canton, Cotopaxi province. Where a diagnosis a was carried out, through a bibliographic review in primary and secondary information sources and the application of two types of surveys allowing the analysis of tourism system and tourist profile demand, in which were determined that adventure and community tourism is one of the most sought-after activities in the canton. The supply has decreased together with the demand, due to the current given conditions by COVID 19 pandemic. Later, an inventory of natural and cultural tourist attractions was carried out (19 cultural attractions and 22 natural ones). With the analysis and obtained information, ecotourism alternatives for each of 41 tourist attractions determined a map of ecotourism alternatives in general where they can be carried out in each tourist attraction designing a catalog of tourist activities with most relevant activities, detailing relevant characteristics such as a summary of photographs and activities that can be carried out in each attraction. Finally, it is concluded that current conditions due to the pandemic have changed tourist preferences regarding the visit of attractions, tourists looking for sources for a safe tourism that applying biosecurity standards to visit any attraction, in addition to planning practice of sustainable tourism activities with the environment, finally, alternatives must be implemented to avoid contagions and that these allowing development of tourism activities safeguarding the health of tourists and people who provide services and products.